Parental Interest in Students’ Achievement in the Subject of English at Early Childhood Stage - Sidra Rizwan, Rehana Rehman (JECCE, 2023)
The article analyzes the interest of parents for the achievement of their children in the subject of English. It was a case study conducted in a private English medium school. The study aimed to find two types of relationships; firstly, the relationship between educational level of parents and achievements of students in the subject of English and secondly relationship between interest of parents and achievement of students in the subject of English. 59 students and their parents (only one of the parents who filled in the questionnaire) participated in the study. It was a census study therefore, 100% sample was taken which consisted of all the pupils and their parents. Pilot testing was conducted on the population with same characteristics. A questionnaire with 26 items for parents was developed and its validity and reliability was determined. Students’ achievement in English was calculated on the basis of English result of the school final term examination. Data collected through questionnaires was analyzed by applying Pearson product moment correlation. The results of correlation showed no relationship between students’ achievement in the subject of English and parents’ educational level, whereas significant relationship was noticed between parental interest and students’ achievement in English.